Understanding Friction and Wear Behaviours of Smooth Resilient Surfaces: Application for Pedestrian Fall Safety Improvements - In-Ju Kim (Advances in Materials Science and Engineering)
The recent literature identified that certain types of smooth floors and flooring materials showed good slip-resistance performance under moderately contaminated situations such as water wet and soapsuds-covered conditions. However, topographic structures of such flat floor/walkway surfaces are significantly changed by wear and tear developments with continuous ambulation. A number of reasons seem to be involved in flooring wear developments, but such changes may result in substantial losses of slip resistance (or traction) functions. Even though the importance of this issue is wide, it is scarce to find any systematic investigations on tribophysical characteristics of smooth floors (<10 µm in Ra roughness) and their wear impacts on traction performance. Moreover, it is difficult to find studies on wear progress of floors and its impacts on pedestrian fall safety assessments. This study focuses on exploring wear activities of smooth resilient floors and disclosing wear consequences on traction properties. To measure slip-resistance features and investigate wear advances of smooth resilient floors, dynamic friction tests were carried out amongst purposely arranged 4 flat specimens (polymethyl methacrylate: PMMA) and 3 shoes. Wear formations and progressions of the PMMA surfaces were methodically evaluated by observing surface profiles during the tests. The test outcomes evidently presented that initial surface features of the PMMA specimens were significantly modified by primary-, secondary-, and shared-wear mechanisms and significantly influenced traction performance. This study may have design applications for the safety enhancements of smooth floors/footpaths to preclude pedestrian fall incidents.